(untitled) (Indian Journal of Animal Production and Management, 2015)
A study was carried out in 54 Large White Yorkshire pigs to find out the effect of early weaning on carcass traits. Three weaning age groups namely group 1 ( 25 days ), group 2 ( 40 days) and group 3( 56 days ) were compared. Each group consists of 18 piglets from three litters. Five months after weaning, six pigs from each group were slaughtered and the carcass traits studied included Pre-slaughter weight, Carcass length, Hot carcass weight, Average Back fat thickness, Dressing percentage, Meat-bone ratio and Whole sale primal cuts. A highly significant (P< 0.01) variation was observed between group 2 and the other two groups with respect to Pre- slaughter weight (64.99 ± 0.30 Kg), Carcass length (26.42 ± 0.27 inches), Average Back Fat Thickness (1.52 ± 0.03 inches), Hot carcass weight (48.86 ± 0.38 Kg), Dressing percentage (75.2 ± 0.39%), Meat - Bone ratio (4.16 ± 0.00), Ham (27.63 ± 0.22 %) and Belly (8.69 ± 0.15 %). Where as Group 3 was higher in Boston butt and Loin and a highly significant variation (P<0.01) was seen with group 2 while Picnic shoulder in group 1 was higher and highly significant (p<0.01) than that of group 2 and 3.